2003
DOI: 10.1007/s00464-001-9231-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term quality of life after laparoscopic and open cholecystectomy

Abstract: The gastrointestinal clinical symptoms were similar in the two groups during the long-term follow-up evaluation, but laparoscopic cholecystectomy was found to be significantly superior to the open technique with respect to the quality of life over the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…Topcu et al (2b) [124] performed a retrospective comparative study on 200 patients. Prior to surgery, both groups were comparable, but 4 years after surgery laparoscopically treated patients reported significantly better QoL in all eight domains of the SF-36.…”
Section: Cholecystolithiasismentioning
confidence: 99%
“…Topcu et al (2b) [124] performed a retrospective comparative study on 200 patients. Prior to surgery, both groups were comparable, but 4 years after surgery laparoscopically treated patients reported significantly better QoL in all eight domains of the SF-36.…”
Section: Cholecystolithiasismentioning
confidence: 99%
“…In minimally invasive surgery alone, it has been used to describe health-related quality of life following laparoscopic cholecystectomy (33), Nissen fundoplication (34), inguinal hernia repair (35), colectomy (36) and gastric bypass (37). In the field of LLDN, Perry et al showed that patients had reached population norms in all eight SF-36 domains by 6 to 12 months (38), but this was the first study to use the SF-36 to describe the recovery process within weeks following the procedure.…”
Section: Standardized Outcomesmentioning
confidence: 99%
“…12,33,51 Minimally invasive lumbar fusion has also been shown to be safe and effective in treating lumbar pathology in elderly patients. 8 However, issues relating to a significant learning curve associated with minimally invasive lumbar fusion have arisen, including increased operative times and higher complication rates, [22][23][24]38,43,46 and concerns persist regarding inadequate neural element decompression during minimally invasive lumbar fusion, resulting in persistent symptoms and a need for reoperation.…”
mentioning
confidence: 99%